POTENSI PENANGKAPAN RADIKAL 2,2-difenil-1-pikril hidrazil (DPPH) OLEH BUAH PISANG SUSU (Musa paradisiaca L. “Susu”) DAN PISANG AMBON (Musa paradisiaca L. “Ambon”) - Anjar Hermadi Saputro; Sudarsono Sudarsono (Majalah Obat Tradisional, 2014)
Nutrients including vitamin A and C on milk banana and ambon banana predicted potential as an antioxidant. This study aims to determine the radical potential of pisang susu and pisang ambon with synthetic vitamin C as a comparison so we get how much antioxidant power of ambon banana and milk banana produced in the fruit if desired pengonsumsian antioxidant power of vitamin C produced by pure at certain levels. This study consisted of measuring the antioxidant activity by the method of 2,2-Diphenyl-1-Pikrilhidrazil (DPPH) so that the data obtained antioxidant activity and Inhibitory Concentration50 (IC50) of milk banana, ambon banana and vitamin C synthetic. From the research results can be concluded that as much as 2418.84g of milk banana as an antioxidant potential equivalent to the antioxidant potential of 1g of vitamin C when measured with 0.4 mM DPPH reagent, while the total of 9229.79g of ambon banana as an antioxidant potential equivalent to the potential antioxidants vitamin C 1 gram when measured with 0.4mM DPPH reagent.